2016
DOI: 10.1016/j.marpol.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

New provisions for the labelling of fishery and aquaculture products: Difficulties in the implementation of Regulation (EU) n. 1379/2013

Abstract: The European Union (EU), within the renewal plan of the Common Fisheries Policy and the Common\ud Market Organization, with the Cape IV of Reg. (EU) n. 1379/2013 have introduced new requirements for\ud the labelling of fisheries and aquaculture products. These, as well as providing consumers with more\ud complete information, integrate the provisions of Reg. (EU) n. 1169/2011 and acts as a tool to prevent\ud frauds and illegal fishing. In this work the new seafood labelling provisions were evaluated, starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 45 publications
(62 reference statements)
0
35
0
1
Order By: Relevance
“…Record keeping can be time-consuming, challenging and beyond the skills of the individuals involved relying on methods and technologies that have remain unchanged for decades. Consequently, the ability to effectively and reliably trace consignments of seafood throughout all supply chains in a consistent manner is challenging (Charlebois et al 2014;Ringsberg 2014;Leal et al 2015;D'Amico et al 2016). Incidences of chain of custody abuse have been reported.…”
Section: Chain Of Custody Abusementioning
confidence: 99%
“…Record keeping can be time-consuming, challenging and beyond the skills of the individuals involved relying on methods and technologies that have remain unchanged for decades. Consequently, the ability to effectively and reliably trace consignments of seafood throughout all supply chains in a consistent manner is challenging (Charlebois et al 2014;Ringsberg 2014;Leal et al 2015;D'Amico et al 2016). Incidences of chain of custody abuse have been reported.…”
Section: Chain Of Custody Abusementioning
confidence: 99%
“…Parasites recovered from products in oil were molecularly identified as A. pegreffii (70.3%) and A. simplex (29.7%). The geographical origin is not compulsory for fishery products in oil (D'Amico et al, 2016) and it was not reported for 5 of the 14 brands. All the larvae molecularly identified from these products were A. pegreffii.…”
Section: Products In Oilmentioning
confidence: 99%
“…Therefore, surimi represents a multispecies seafood product, as its production can imply the use of an extremely wide range of species [2,5]. According to the current EU law on food labelling, it is not mandatory to provide the commercial and/or scientific name of the seafood species present in SBPs [9–11], although some brands report it voluntarily (author’s note). However, the presence of ingredients potentially causing allergies, listed in the Regulation (EU) No 1169/2011 (including “fish” and “molluscs”) must be declared.…”
Section: Introductionmentioning
confidence: 99%